Developing a self-care program for individuals with type 2 diabetes in Uttaradit - ภมะราภา, อายุส (Journal of Health Science of Thailand, 2025)
Developing a self-care program for individuals with type 2 diabetes in Uttaradit Aryoot Pamarapa Internal medicine Uttaradit Hospital Abstract Type 2 diabetes mellitus is the most prevalent chronic disease globally, including Thailand. The rise in Type 2 diabetes cases is linked to unhealthy lifestyle behaviors. This research was conducted to evaluate the effectiveness of a self-care program for individuals with type 2 diabetes in controlling blood glucose levels and reducing the risk of complications. This quasi-experimental study employed a one-group time series design to evaluate the effects of the intervention. Forty participants were purposively selected and followed for 36 weeks. This program was developed based on findings from the Phase 1 study. It incorporates variables that were found to have a statistically significant impact (p < 0.05) on self-care behaviors among individuals with type 2 diabetes. The program consists of four primary components: 1) education to enhance health knowledge and promote a better understanding of the condition; 2) skill-building activities to improve self-management capabilities; 3) motivational support and reminders to reinforce healthy behaviors; and 4) the development of self-efficacy to empower individuals to take control of their health. Data were collected through questionnaires and behavioral assessments. To test the research hypotheses, pre- and post-intervention data were compared. Descriptive statistics including frequency, percentage, mean, and standard deviation were computed. Paired t-tests were employed to determine the statistical significance of changes between the pre- and post-intervention measurements. Prior to the intervention, the analysis of participants' mean blood glucose levels revealed that 0% were categorized as having good control, 39% as having fair control, and a majority of 61% as having poor control. Post-intervention analysis revealed a notable improvement in glycemic control among participants. The proportion of individuals categorized as having good control increased by 31.24%, those with fair control increased by 42.45%, and the proportion of those with poor control significantly decreased to 26.37%. A comparison of pre- and post-intervention HbA1c levels revealed a statistically significant difference (p < 0.05), indicating a substantial improvement in glycemic control following the intervention. The self-care intervention implemented in Uttaradit province demonstrated a positive impact on the self-care behaviors of individuals with type 2 diabetes. Participants exhibited significant improvements in various aspects of self-care, and their blood glucose levels were successfully lowered to a safer range. Keywords: Self-care program, Blood glucose level, Type 2 diabetes.